Trait Kepribadian dan Komitmen Afektif pada Kepanitiaan Psycompilation 2020 - Joshua Aditya Putra Utama; Ria Wardani (Universitas Kristen Maranatha, 2020)
This research uses the theory of The Big Five Personality Traits (McCrae & Costa, 1997) and Affective Commitment (Meyer & Allen, 1997) to determine the correlation between Personality Traits and Affective Commitment on the committee of Psycompilation 2020. There were 84 committees who participated in this research. Each respondent filled out the Big Five Inventory (BFI) – 10 Questionnaire (Rammstedt & John, 2007) and Affective Commitment Questionnaire (Organizational Commitment Questionnaire) (Meyer & Allen, 1997). The data from both variables were tested for correlation using the Spearman’s Rho correlation test. It was found that Extraversion, Agreeableness, Conscientiousness, and Neuroticism Traits are correlated to Affective Commitment. In addition, the reasons for participating in the committee are also correlated to Affective Commitment. For further similar research, it is suggested to consider the diversity of organizational characteristics and personal characteristics, which also affect The Affective Commitment. Keywords: Affective Commitment, Personality Traits, Psycompilation, Student Organization